Transcriptome profiling based on Illumina- and SMRT-based RNA-seq reveals circadian regulation of key pathways in flower bud development in walnut - Kai Ma (Public Library of Science (PLoS), 2021)
Flower bud development is a defining feature of walnut, which contributes to the kernel yield, yield stability, fruit quality and commodity value. However, little is known about the mechanism of the flower bud development in walnut. Here, the stages of walnut female flower bud development were divided into five period (P01-05) by using histological observation. They were further studied through PacBio Iso-Seq and RNA-seq analysis. Accordingly, we obtained 52,875 full-length transcripts, where 4,579 were new transcripts, 3,065 were novel genes, 1,437 were consensus lncRNAs and 20,813 were alternatively spliced isoforms. These transcripts greatly improved the current genome annotation and enhanced our understanding of the walnut transcriptome. Next, RNA sequencing of female flower buds at five periods revealed that circadian rhythm-plant was commonly enriched along with the flower bud developmental gradient. A total of 14 differentially expressed genes (DEGs) were identified, and six of them were confirmed by real-time quantitative analysis. Additionally, six and two differentially expressed clock genes were detected to be regulated by AS events and lncRNAs, respectively. All these detected plant circadian genes form a complex interconnected network to regulate the flower bud development. Thus, investigation of key genes associated with the circadian clock could clarify the process of flower bud development in walnut.